Chondrosarcoma of the Posterior Mediastinum: A Rare Case Report - Yıldırım, Mustafa; Koc, Mustafa (My University, 2020)
Chondrosarcoma is a malignant mesenchymal tumor originating from cartilage and it producescartilage matrix. The cartilage of the pelvis and long bones most frequently affected sites. Posteriormediastinum is a rare localization for chondrosarcoma. The symptoms of posterior mediastinumchondrosarcoma are nonspecific. Also, the differential diagnosis of posterior mediastinal masses isextensive. Therefore, radiological imaging plays an important role in the diagnosis. In this report, acase of chondrosarcoma originating from posterior mediastinum was presented with imagingfindings.
Keywords: Genel ve Dahili Tıp; Patoloji; Onkoloji